Habitat occupancy of the Dusky-legged Guan in the lower delta of the Paraná River, Argentina - Malzof, Silvina L. (2013)
Summary The Dusky-legged Guan Penelope obscura is the southernmost species of the family Cracidae, reaching its southern distributional limit in the delta of the Paraná River. Habitat loss, together with uncontrolled harvest, has led to local-scale decreases or extirpation of the species, but no quantitative evaluation of habitat preferences has been made. We surveyed Dusky-legged Guans in the Delta del Paraná Biosphere Reserve, Argentina, by motorboat along 543.9 km of nine waterways during both January and July 2009 and used occupancy modelling to estimate habitat and seasonal effects on occupancy. Detectability was 21-22% on average and occupancy estimates were highly variable within habitats, but highest in secondary forest, followed by mature plantation, and lowest in occupied residences. There were no significant differences in occupancy or detectability among habitats or seasonally. There was a strong positive effect of length of riparian habitat segments on occupancy and detectability. Habitat management efforts should address increasing the suitability of mature plantation forest for guans by increasing their similarity to native forest in structure and composition. Furthermore, we illustrate that surveys by boat can be logistically effective for surveying cracids associated with riverine habitats and that it is important to account for incomplete detectability since in our case failing to do so would have underestimated occupancy by 78-79% on average. Given this, the use of commonly accepted methodologies for surveying cracids that do not account for incomplete detectability should be reconsidered and methodologies that can produce robust, reliable estimates applied. Copyright © BirdLife International 2012.